Handbook of rituals in contemporary studies of religion: exploring ritual creativity in the footsteps of Anne-Christine Hornborg - Brissman, Ive; Linjamaa, Paul; Thykier Makeeff, Tao ca. 21. Jh. (Brill handbooks on contemporary religion, 2024)
"This book brings together leading international scholars with the aim of exploring ritual perspectives in the study of contemporary religions. It combines significant theoretical and methodological reflections and applies it to four main fields relevant to the study of contemporary religions: indigeneity; new spiritualities and ecology; lived religion (with Islam and Africa as case studies); and finally, religion and embodiment. The structure and content of the book takes its point of departure from the research topics and collegial network of the internationally acclaimed scholar of ritual studies, Professor Anne-Christine Hornborg. The book is dedicated to her"--